Pengembangan Metode Identifikasi Sianida Pada Bahan Pangan - Fransiska Ayuningtyas Widyastani; Gerda Erina Ayu Widyastuti; Endang Hariyani; Fransisca Probo Setyoningrum (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2025)
Cyanide (CN-) is a compound that is commonly found in food and can cause health problems and reduce the bioavailability of nutrients in the body and even death, so the presence of cyanide needs to be controlled.Ninhydrin functions as a cyanide complexing reagent formed from the oxidation of thiocyanate which can be used to identify the presence of cyanide. This study aims to develop a cyanide identification method using the ninhydrin cyanide test kit. The test kit is a tool that can be used to detect levels of a compound quite accurately which is easy to use and operate by various groups. The reaction of ninhydrin with cyanide forms hydrindantine which will give a red color to the strip containing Na2CO3. This study uses a qualitative method with the type of pre-experimental research. The results of the data obtained were analyzed using a descriptive test that uses a pie chart frequency so that the results for cassava were positive at 93.3%, while the results were negative at 6.67%. So from this research it can be concluded that the development of a cyanide examination method using the Ninhydrin Test Kit method can be used to identify samples that are suspected to contain free cyanide qualitatively.